"الإفتاء باتيسير للاقليات المسلمة في الأحوال الشخصية عند القرضاوي "دراسة تحليلية نقدية - Husnul Haq (MAHAKIM Journal of Islamic Family Law, 2020)
The Muslim minorities in non-Muslim countries face many problems. The most important of which are religious problems. They want to deal with non-Muslims, without taking away their Islamic personality. They are in dire need of a fatwa that is easy and tolerant, away from narrowing and embarrassment. Contemporary scholars, especially syekh Yusuf Qaradhawi, respond this need, and issue fatwas, which are easy and tolerant. The research aims to clarify the principle of facilitation in the fatwas of contemporary scholars with regard to Muslim minorities in the field of personal status, and the suitability of this principle to the principle of facilitation in Islamic Jurisprudence. The character of the research is a descriptive, analytical, and critical. The researcher concludes that the scholars adhered to the principle of facilitation in their fatwas for Muslim minorities, in the field of personal status. And the best testimony to that is the fact that they have stated that it is permissible for a woman to remain with her non-Muslim husband, and that they are allowed to legalize the inheritance of a non-Muslim. The facilitation adopted by them is commensurate with the facilitation of Islamic jurisprudence, its principles and purposes, because it stands on the principle of taking into account of necessity, need, license, rule of origin, and changing the ruling by changing its cause.